Effects of low-carbohydrate diets versus low-fat diets on metabolic risk factors in overweight and obese adults: A meta-analysis of randomized controlled trials - Lei, Lifu; Huang, Juan; Zhang, Longlong; Hong, Yuqin; Hui, Suocheng; Yang, Jian (Frontiers in Nutrition, 2022)
Background and aims: Both low carbohydrate diets (LCD) and low fat diets (LFD) have shown beneficial effects for the management of obesity. Epidemiological studies were conducted to compare the effects between the two diets. however, the results were not always consistent. The aim of this study was to conduct a meta-analysis to compare the effects of LCD and LFD on metabolic risk factors and weight loss in overweight and obese adults. Methods: We performed a systematic literature search up to 30 March 2022 in PubMed, EMBASE and Cochrane Library. The meta-analysis compared the effects of LCD (carbohydrate intake ≤ 40%) with LFD (fat intake ≤ 30%) on metabolic risk factors and weight loss over a period of ≥ 6 months. Subgroup analyses were performed based on participant characteristics, dietary energy intake and proportions of carbohydrates. Results: 33 studies involving a total of 3939 participants were included. Compared with participants on LFD, participants on LCD had a greater reduction in triglycerides (-0.14 mmol/L; 95% CI, -0.18 to -0.10 mmol/L)，diastolic blood pressure (-0.87 mmHg; 95% CI, -1.41 to -0.32 mmHg), weight loss (-1.33 kg; 95% CI, -1.79 to -0.87 kg), and a greater increase in high-density lipoprotein cholesterol (0.07mmol /L; 95% CI, 0.06 to 0.09 mmol/L) in 6-23 months. However, the decrease of total cholesterol (0.14 mmol/L; 95% CI, 0.07 to 0.20 mmol/L) and low-density lipoprotein cholesterol (0.10 mmol/L; 95% CI, 0.06 to 0.14 mmol/L) were more conducive to LFD in 6-23 months. There was no different benefit between the two diets after 24 months. Subgroup analyses showed that there was no significant difference in the reduction of total cholesterol, low-density lipoprotein cholesterol and blood pressure between two diets in participants with diabetes, hypertension or hyperlipidemia. Conclusion: The results suggest that LCD and LFD may have specific effects on the metabolic risk factors and weight loss in overweight and obese adults. These indicated that we may choose different diets to manage the overweight and obese subjects. However, the long-term effects and effects of various sources of carbohydrates or fat in the two diets need to be studied in the future.